FOTOGRAMMETRIA DA UAV PER INTEGRARE IL RILIEVO E LA DOCUMENTAZIONE DI MONUMENTI COLPITI DA SISMA - Balletti, Caterina; Guerra, Francesco; Vernier, Paolo (GEOmedia, 2014)
The aim of this article is to focus on the application of new technologies and methodologies in delicate contexts such as areas stroke by earthquakes. This article describes the first results of a survey campaign on the Church of San Geminiano in San Felice sul Panaro (Modena) that was almost completely destroyed by the last earthquake. In this case, different tools and methodologies have been used in order to create an integrated system of all the most recent technologies used in Geomatics. Often, due to the complexity of contexts and the buildings' geometry it is necessary to use the most recent structural techniques, encouraging research both during data collection and during further elaboration processes. It is indeed necessary to integrate different survey techniques in order to obtain a complete documentation of the object studied, as the Laboratorio